Effect of prehospital transport factors on shock index, serum lactate, and mortality in children with septic shock: A prospective observational study - Sankar, Jhuma; Das, Rashmi; Singh, Archana (Journal of emergencies, trauma and shock, 2019)
Context: Many children with septic shock either present late or are recognized late due to various reasons. Shock index (SI) is a valuable screening tool in dentifying high-risk septic patients in emergency department. Whether prehospital transport factors affect SI and clinical outcomes has not been evaluated. Aim: Our aim was to evaluate if prehospital transport-related factors such as mode of transport and referral from another hospital affect the admission SI and mortality in children with septic shock. Settings and Design: Prospective observational study conducted over 1-year period in the Pediatric Emergency and Intensive Care Unit of a tertiary care teaching hospital. Subjects and Methods: Children < 17 years of age were evaluated. Data collection included referral status, mode of transport, physiologic (SI and serum lactate), and clinical parameters. Statistical Analysis Used: Student's t-test was used for analyzing continuous variables. Chi-square/Fischer's exact test was used for analysis of categorical variables. P < 0.05 was considered as statistically significant. Results: Of 51 children, 21 (41%) were referred from other hospitals. Of these, less than half were transported by ambulance unaccompanied by any healthcare personnel. Twenty-six children (43%) died, of which 15 (71%) were referred. The median serum lactate, SI, and mortality were significantly higher in those referred. On multivariate analysis of factors associated with mortality, elevated SI and/or lactate >4 mmol/L and the "referral" status remained significant after adjusting for baseline variables and illness severity. Conclusions: Children with septic shock referred from other hospitals had higher SI, serum lactate, and mortality rates. Our study highlights the need for improving prehospital care and transportation in children with septic shock.